Modelos dendrométricos e avaliação do crescimento individual em povoamentos clonais de Eucalyptus spp. na região oriental do Paraguai - Acosta, Hugo Armando Barúa (2019)
The development of the forestry sector is recent in Paraguay, and is based in clonal plantations of Eucalyptus. Considering the lack of studies regarding the growth of clonal plantations, this research aimed to adjust dendometric and growth models to clonal plantations of Eucalyptus spp., sorted in three genotypes groups in two districts in the oriental region of Paraguay. The evaluated plantations were in the districts of Hernandarias (Location 1) and San Juan Nepomuceno (Location 2), considering three groups of genotypes (13 clones) in the Location 1, and three groups of genotypes (10 clones) in the Location 2. The data are from permanent inventory plots of 1,000 m² of plantations with ages ranging from 12 to 93 months. Besides the data from permanent plots, were used data of strict cubing of 331 trees of the Location 1 and of 94 trees of the Location 2. Volume of the cubed trees was determined by the Smalian method, measuring heights at 0.10 m; 0.50 m; 1 m; 1.30 m; 2.0 m and from this in each 1.0 m, obtaining the total volume of each tree. Hypsometric relation, volumetric, taper and site index models along with the model of Chapman-Richards were adjusted to construct growth and production curves, applied for the genotypes groups with the following dendometric variables: mean arithmetic height, mean arithmetic diameter, and mean arithmetic volume. For each model type the identity test was applied, aiming to cluster the genotypes groups and the locations. It is concluded that the modelling showed appropriated results for the adjust and precision statistics, in which the model of Campos had the better adjust to estimate height, and the equation of Schumacher and Hall to estimate total volume. The models adjusted independently also showed appropriated results, as the fifth-degree polynomial model to estimate the longitudinal profile of the stems, and the model of Schumacher to construct the site index curves. The model of Chapman-Richards estimated precisely the growth of the evaluated dendometric variables. The identity test showed that the same site index equation can be applied for the two locations, whereas the hypsometric and tapering models, and the dendometric variables cannot be expressed by a single equation.